The Rules of Everything - Templar, Richard, 1950-2006 (Pearson Education, Limited, 2022)
Whether it's at work or in their relationships, as parents or managing their money, the Rules have described how happy and successful people behave for over 25 years. The Rules of Everything contains the top 100 rules from the bestselling Rules books, as voted for by readers, so you can follow the common-sense advice on how to be happier and more successful.